Perfil socioeconómico de las productoras y los productores de quinua en el Altiplano Sur de Bolivia, 2023 - Daniela Romero Romay; María Cecilia Lenis Abastoflor (Institute for Advanced Development Studies (INESAD), 2024)
– The drop in quinoa prices during 2015 caused a deep economic and environmental crisis that forced producers to seek new sources of income and marketing strategiesto achieve production sustainability. Under these circumstances, women producers also had to seek a beter balance between their tasks inside and outside their homes. In 2020, the COVID-19 pandemic brought many economic activities to a standstill, generating an economic shock which, in the case of agricultural products, was mainly related to transportation shortages. Likewise, many households suffered the loss of their sources of labor, facing a reduction in their incomes. Women, for their part, tripled their working hours due to the need for greater care coming from all members of the house during confinement. Thus, quinoa producers were affected by various crises over the last 8 years. Given these conditions, the purpose of preparing a socioeconomic profile about such producers isto characterize their current socioeconomic situation and, by this way, to provide key elements for proposing recovery strategies based on good agricultural practices that may promote environmental and economic sustainability in the sector. In addition, the analysis includes the gender approach in order to distinguish the roles played by men and women in production and the promotion of these productive practices.
Keywords: C8; D2; G83; I2; J43; I1; 330; Socioeconomic profile; quinoa production; gender; education; employment; health